PTU-134 What do young people and parents want from an inflammatory bowel disease (IBD) service?. (28th May 2012) - Little, R; Imrie, C; Derby, A; Gillespie, P; Caddy, G R; Tham, T C
Abstract : Introduction: At present, there are guidelines from the US and Europe regarding the formation of transition clinics for adolescents with IBD. This includes a UK Inflammatory Bowel Disease (IBD) Standards guidance on optimal service provision for paediatric and adolescent care. However most of these guidelines come from intuitive reasoning and opinion, as there is a lack of data on what constitutes an ideal service for young patients with IBD. The aim of this study was to develop a comprehensive knowledge and understanding of the key service requirements of young people with IBD as well as their parents. Methods: Paediatric and adolescent patients age 6–18 years, were identified from databases in two teaching hospitals and from the membership of the N Ireland branch of Crohn's and Colitis UK, which is a patient support group. Anonymous questionnaires were sent to these patients and their parents separately. The questionnaires asked about their perceived quality of care, clinic care, general comments, input from specialists, support and information, plus any suggestions. Results: 105 questionnaires were sent and 51 responded (49%); of these 21 were from patients and 30 from their parents. Over 84% were happy with the quality of care they are receiving. Reasons patients and parents were reluctant to attend clinics included: blood tests, nurse specialist or doctor not available, lack of car parking. 90% preferred to see the attending (Consultant) rather than a fellow. Nurse specialist, dietetics, specialist IBD surgeon, psychologist, skin/eye specialist input was thought to be beneficial by 95%, 81%, 71%, 59%, and 45% respectively. The following support service and information were considered important: immediate contact with healthcare personnel for disease flare, support groups for young adults, insurance and financial advice, knowledge about IBD developments and research, email service, surgical input regarding stomas. Conclusion: The majority of young patients with IBD and their parents are satisfied with the care they are receiving. Support from specialist services such as nurse specialist, dietitians, specialist IBD surgeons, psychologist, plus rapid access to services when the disease flares were thought to be important by the patients and their parents. Knowledge of what these patients and their parents want will help to design an optimal IBD service. Competing interests: R Little: None Declared, C Imrie Conflict with: Mead Johnson, Falk Pharma, Nutricia, Warner Chilcott, SHS, Norgine, Wyeth, A Derby: None declared, P Gillespie: None declared, G Caddy: None declared, T Tham Speaker bureau with: Warner Chilcott, Shire, Conflict with: Abbott, MSD.